Basics on Commodities Risk Management for Grains Trading - Giruć, Piotr (Journal of Finance and Financial Law, 2016)
The purpose of the article is to determine the kinds of risk groups existed on cereal market and presenting possibilities of limiting the undesirable phenomena. An issue appears: what way the subjects of cereal market, producers in particular, should alone neutralize the appearing risk, and when should expect support from the state institutions. More often financial instruments find the solution for agricultural hedgers. Derivatives, such as: forward, future and option contracts are transferring the price risk from producers to intermediaries of the market and are improving the flow of contracts on the cereal market.